Characterization of a novel 2D array dosimeter for patient‐specific quality assurance with volumetric arc therapy. Issue 7 (1st July 2013) - Stathakis, Sotirios; Myers, Pamela; Esquivel, Carlos; Mavroidis, Panayiotis; Papanikolaou, Nikos
Abstract : Purpose: : In this study, the authors are evaluating a new, commercially available 2D array that offers 3D dose reconstruction for patient specific intensity modulated radiation therapy quality assurance (IMRT QA). Methods: : The OCTAVIUS 4D system and its accompanying software (VERISOFT ) by PTW were evaluated for the accuracy of the dose reconstruction for patient specific pretreatment IMRT QA. OCTAVIUS 4D measures the dose plane at the linac isocenter as the phantom rotates synchronously with the gantry, maintaining perpendicularity with the beam, by means of an inclinometer and a motor. The measurements collected during a volumetric modulated arc therapy delivery (VMAT) are reconstructed into a 3D dose volume. TheVERISOFT application is used to perform the analysis, by comparing the reconstructed dose against the 3D dose matrix from the treatment planning system (TPS) that is computed for the same geometry and beam arrangement as that of the measurement. In this study, the authors evaluated the 3D dose reconstruction algorithm of this new system using a series of tests. Using the Octavius 4D phantom as the patient, dose distributions for various field sizes, beam orientations, shapes, and combination of fields were calculated using the Pinnacle3, TPS, and the respective DICOMRT dose was exported to theVERISOFT analysis software. Measurements were obtained by delivering the test treatment plans and comparisons were made based on gamma index, dose profiles, and isodose distribution analysis. In addition, output factors were measured and the dose linearity of the array was assessed. Those measurements were compared against measurements in water using a single, calibrated ionization chamber as well as calculations from Pinnacle for the same delivery geometries. Results: : The number of voxels that met the 3%/3 mm criteria for the volumetric 3D gamma index analysis ranged from 92.3% to 98.9% for all the patient plans that the authors evaluated. 2D gamma analysis in the axial, sagittal, and coronal planes produced similar results to those in the 3D gamma analysis. The new detector system does not require an angular dependence correction because it rotates in synchrony with the gantry and the detector array maintains a constant SAD while always perpendicular to the beam axis. Output factors were within 2% when compared to ionization chamber measurements and Pinnacle calculations. Similar agreement was observed when testing the MU linearity (for MU values above 2) as well as dose rate effect. Conclusions: : The OCTAVIUS 4D system has some unique characteristics that can potentially improve the patient specific pretreatment IMRT QA data collection and analysis. The ability of the software to reconstruct from the measurements the true 3D dose distribution in the phantom, provides a unique perspective for the medical physicist that evaluates a patient's QA plan.